2010
DOI: 10.2175/106143009x12529484815511
|View full text |Cite
|
Sign up to set email alerts
|

Data Reconciliation for Wastewater Treatment Plant Simulation Studies—Planning for High‐Quality Data and Typical Sources of Errors

Abstract: Model results are only as good as the data fed as input or used for calibration. Data reconciliation for wastewater treatment modeling is a demanding task, and standardized approaches are lacking. This paper suggests a procedure to obtain high‐quality data sets for model‐based studies. The proposed approach starts with the collection of existing historical data, followed by the planning of additional measurements for reliability checks, a data reconciliation step, and it ends with an intensive measuring campai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…Experience showed that a detailed characteristic of influent wastewater was essential for effective model calibration and successful simulations (Xu and Hultman 1996;Mikosz 1999;Pasztor et al 2009;Mąkinia 2010;Rieger et al 2010). During the research/study, all influent streams were defined with the 'tsscod' influent model, originally developed based on the Activated Sludge Model no.…”
Section: Modelling Toolsmentioning
confidence: 99%
“…Experience showed that a detailed characteristic of influent wastewater was essential for effective model calibration and successful simulations (Xu and Hultman 1996;Mikosz 1999;Pasztor et al 2009;Mąkinia 2010;Rieger et al 2010). During the research/study, all influent streams were defined with the 'tsscod' influent model, originally developed based on the Activated Sludge Model no.…”
Section: Modelling Toolsmentioning
confidence: 99%
“…As a result, the resources e both in terms of time and capital e spent on installing and maintaining on-line sensors, and on collecting and storing online data in databases, are to a large extent lost since the collected data is not transformed into actionable knowledge for system optimization. Despite the historical recognition of the need for high quality data (Rieger et al, 2010), sub-optimal operation of a WWTP is still the norm rather than the exception. This situation is unacceptable given the need for an efficient, resilient, and sustainable use of available resources.…”
Section: Introductionmentioning
confidence: 99%
“…A data reconciliation approach was proposed Rieger et al (2010a) in order to identify systematic measurement errors with intensive measurement campaigns after all mass balances applied to the historical data are closed or after data faults have been detected, isolated, and identified. Velmurugan et al (2010) developed a reducedorder model for the design of organic and nitrogen substrates in a sequencing batch reactor (SBR).…”
mentioning
confidence: 99%